Applying differential equations for study magnetohydrodynamic phenomenon on the solar surface. Issue 1 (April 2021) - Sujito, S; Wisodo, H; Pratiwi, H Y; Setyahadi, B; Soewono, E; Suhandi, A; Liliasari, L
Abstract: The aim of this research is to study the magnetohydrodynamic (MHD) phenomenon on the solar surface by apply differential equations. We are trying to understand and explain the processes from observable solar layers to deeper layers, by using plasma theory and data analysis that may construct understandings to solar physics. This research is done by combining the MHD simulation and data of solar observation results. MHD simulation was carried out in the theoretical laboratory, physics department, UM. Data on the sun's observation were obtained from LAPAN Watukosek Jawa Timur. The results of this study are the coronal solar helmet streamer structure is degraded and the MHD equilibrium ends before it erupts. This is shown by the simulation results using data obtained from observations, namely the degradation of colors from the strongest to the weakest. This shows the existence of weakening energy before finally experiencing an eruption. The phase was terminated by the coronal mass eruption (CME). Activity to the surface of the corona to the inner layer is outside our technology to observe directly. Therefore, the conclusions in this article are made using the plasma flow approach at high temperatures.